A 0.015 kg marble sliding to the right at 22.5 cm/s on a frictionless surface makes an elastic head-on collision with a 0.015 kg marble moving to the left at 18.0 cm/s. After the collision, the first marble moves to the left at 18.0 cm/s.
A. Find the velocity of the second marble after the collision.
B. Verify your answer by calculating the total kinetic energy before and after the collision.

Respuesta :

Answer:

Explanation:

mass of first marble [tex]m_1=m=0.015\ kg[/tex]

Initial velocity of the first marble [tex]u_1=22.5\ m/s[/tex]

considering right side as positive

Mass of second marble

[tex]m_2=m=0.015\ kg\\u_2=-18\ cm/s[/tex]

After collision first marble moves to the left with a velocity of 18 cm/s

i.e. [tex]v_1=-18\ cm/s[/tex]

considering [tex]v_2[/tex] be the velocity of second marble after collision

The Coefficient of restitution is 1 for an elastic collision

[tex]e=\frac{v_2-v_1}{u_1-u_2}[/tex]

Putting values

[tex]1=\frac{v_2-(-18)}{22.5-(-18)}\\22.5+18=v_2+18\\v_2=22.5\ m/s[/tex]

So, the velocity of the second marble is 22.5 m/s to the right after the collision

(b)Initial kinetic energy =[tex]0.5\times 0.015\times (22.5\times 10^{-2})^2+0.5\times 0.015\times (18\times 10^{-2})^2=6.22\times 10^{-4}\ J[/tex]

Final kinetic energy=

[tex]0.5\times 0.015\times (18\times 10^{-2})^2+0.5\times 0.015\times (22.5\times 10^{-2})^2=6.22\times 10^{-4}\ J[/tex]

(A) The velocity will be "22.5 m/s".

(B) The initial as well as the final K.E will be "6.22×10⁻⁴ J".

Given:

First marble:

  • Velocity, [tex]u_1 = 22.5 \ m/s[/tex]
  • Mass, [tex]m = m_1 = 0.015 \ kg[/tex]

Second marble,

  • Velocity, [tex]u_2 = -18 \ cm/s[/tex]
  • Mass, [tex]m = m_2 = 0.015 \ kg[/tex]

(A)

As we know, the coefficient of restitution will be:

→ [tex]e = \frac{v_2-v_1}{u_1-u_2}[/tex]

By putting the values,

  [tex]1 = \frac{v_2-(-18)}{22.5-(-18)}[/tex]

By applying cross-multiplication,

 [tex]22.5+18=v_2+18[/tex]

            [tex]v_2 = 22.5 \ m/s[/tex] (velocity)

(B)

The initial K.E:

= [tex]0.5\times 0.015(22.5\times 10^{-2})^2+0.5\times 0.015(18\times 10^{-2})^2[/tex]

= [tex]6.22\times 10^{-4 \ J[/tex]

The final K.E:

= [tex]0.5\times 0.015(18\times 10^{-2})^2+0.5\times 0.015(22.5\times 10^{-2})^2[/tex]

= [tex]6.22\times 10^{-4 \ J[/tex]

Thus the responses above is right.

Learn more about collision here:

https://brainly.com/question/25786281